Dietary habits and thyroid cancer risk: A hospital-based case–control study in Sicily (South Italy). (December 2020) - Fiore, Maria; Cristaldi, Antonio; Okatyeva, Valeria; Lo Bianco, Salvatore; Oliveri Conti, Gea; Zuccarello, Pietro; Copat, Chiara; Caltabiano, Rosario; Cannizzaro, Matteo; Ferrante, Margherita
Abstract: Several studies have investigated the role of diet as a risk and/or protective factor against thyroid cancer, both considering individual foods, groups of foods and dietary patterns, but the results are not consistent. The aim of the study was to investigate the relationship between dietary habits and thyroid cancer. Cases and controls were recruited at the University Hospital "G. Rodolico" of Catania. The dietary habits were defined through the "Lifestyle Assessment Questionnaire". The frequency of consumption of each food item was reported on a 4-level scale (never, one time a week, 2–3 times a week, every day of the week). We computed the odds ratios (ORs) of thyroid cancer and the corresponding 95% confidence intervals (CIs) according to the median of control group daily intake of each food group, using multiple logistic regression models adjusted for major confounding factors. Starchy foods (OR = 1.39, 95% CI 0.83–2.32), sweets (OR = 1.39, 95% CI 0.81–2.40) and products rich in salt and fat showed a positive association with thyroid cancer risk. Conversely, an inverse association with disease risk was found for vegetables (cruciferous OR = 0.30, 95% CI 0.10–0.92, non cruciferous OR = 0.57 (0.20–1.57) milk and dairy products (OR = 0.68, 95% CI 0.40–1.13) and seafood (OR = 0.68, 95% CI 0.34–1.22). An increased risk was observed for consumption of iodized salts (OR 2.06, 95% CI 1.21–3.51), tea (OR = 1.42, 95% CI 0.84–2.41) and coca-cola (OR = 3.08, 95% CI 1.53–6.20). Finally, our results confirm the protective effect of a daily water intake of 1–2 L, but unfortunately this quantity is usually consumed by about a quarter of the sample. Dietary habits appear to modify the risk of thyroid carcinoma. A diet with a limited consumption of starchy foods, products rich in salt, fat and sugar and a higher consumption of, cruciferous/non-cruciferous vegetables, milk and dairy products and seafood could be protective towards thyroid cancer. Moreover, the water intake should be increased and the actual need to consume iodized salt should be verified for each subject/area. These results warrant further investigations and, if confirmed, they might have important public health implications for the reduction of thyroid cancer through the improvement of dietary habits.